Delayed diagnosis of oculopharyngeal muscular dystrophy in Scotland. Issue 2 (20th May 2011) - Agarwal, Pankaj Kumar; Mansfield, David C; Mechan, Dorothy; Al-Shahi Salman, Rustam; Davenport, Richard J; Connor, Myles; Metcalfe, Richard; Petty, Richard
Abstract : Introduction: Oculopharyngeal muscular dystrophy (OPMD) presents with progressive ptosis, dysphagia and limb girdle weakness, and is caused by expansion of a trinucleotide tandem repeat within the gene encoding poly-(A) binding protein 2. Aim: To review the clinical manifestations of all genetically confirmed patients with OPMD in Scotland identified since 2002, and to estimate the delay between symptom onset and diagnosis. Method: Retrospective case note review. Results: The authors identified 17 patients. The commonest first symptom was ptosis at about the age of 60 years. Three to 20 years elapsed from the onset of ptosis to OPMD diagnosis. In 14 (82%) patients, dysphagia had developed by the time of diagnosis, and four (24%) out of these 14 patients with dysphagia had undergone a decade of investigation and treatment for pharyngeal problems. Thirteen patients (77%) also had symptoms of limb girdle muscle weakness. Every patient had a first-degree relative with ptosis. Conclusions: OPMD could have been diagnosed earlier in every patient in this case series. Greater awareness of OPMD among ophthalmologists, gastroenterologists and otolaryngologists may lead to earlier diagnosis, improved management and avoidance of unnecessary investigations.